The fundamental principle of human dignity and its performance as a general clause for the protection of the personality (Revista do Tribunal Regional Federal da 3ª Região, 2023)
The text analyses the fundamental principle of the dignity of the human person and its performance as a general clause of protection of the personality. For that, it uses a descriptive and deductive methodology, based fundamentally on bibliographic and legislative research. The paper initially presents a brief evolution of the idea of dignity. It investigates the existential relation between the constitutionalisation of private law and the inclusion of the human dignity as a constitutional principle. It also examines the distinction between general clauses and principles, but makes it clear that the human dignity is, at the same time, a general clause and a principle. Finally, results demonstrate the importance of recognizing the human dignity as a true general clause of protection and promotion of the human person.
Keywords: Dignity of human person; Personality rights; Constitutionalization of private law; General clause